Perceptions, knowledge and practices in oral health: An integrative review (Research, Society and Development, 2024)
Throughout life, it is necessary to address hygiene and dietary habits as a form of oral health prevention, ensuring that these teachings are consolidated in both school and home environments. Thus, the objective was to verify, through a literature review, the oral health of schoolchildren, focused on both their knowledge and perceptions. This study employs an integrative literature review methodology. Searches were conducted on the "Google Scholar" platform, and the review was constructed using DECS terms such as "oral health or dental health," "schoolchildren or children or adolescents," "prevalence," and "caries." The findings revealed that the knowledge acquired by schoolchildren primarily comes from interactions with oral health professionals and family members, with a small contribution from schools. Additionally, it was identified that students from lower-income families or those living in peripheral areas have poorer oral health compared to schoolchildren from higher-income families and those attending central schools. Furthermore, the DMFT (Decayed, Missing, and Filled Teeth) index was found to be low but with a tendency to increase, indicating the need for preventive and care measures to maintain health promotion.